Diagnostic Accuracy of CT Scan for Detection of Cervical Lymph Node Metastasis in Oral Squamous Cell Carcinoma in Comparison with Histopathological Analysis After Neck Dissection - Mirmohammad Sadeghi, Hassan; Pournabi, Alireza; Namdari, Mahshid (Journal of Dental School, 2019)
Objectives: Presence/absence of cervical lymph node metastasis plays a critical role in prognosis and survival of patients with oral squamous cell carcinoma (SCC). This study was designed to assess the diagnostic accuracy of computed tomography (CT) scan for detection of cervical lymph node metastasis in oral SCC in comparison with histopathological analysis after neck dissection. Methods: In this retrospective cross-sectional study, pathology and CT reports of 50 patients with oral SCC were retrieved from the archives of Taleghani and Shariati Hospitals and data regarding the site of involvement, lymph node metastasis, level of cervical involvement and size of involved lymph node were retrieved from patient files. The results of CT scan and pathology reports were compared and the accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of CT scan were calculated compared to the gold standard (pathology report). Basic statistics was meed for analyz the data. Results: The sensitivity of CT scan for detection of metastatic cervical lymph nodes was 69.23% compared to the pathology report (gold standard). The specificity, PPV and NPV were 27.02%, 25% and 71.42%, respectively. The diagnostic accuracy of CT scan was 38%. Conclusion: Based on the results, CT scan is not reliable for detection of metastatic cervical lymph nodes in oral SCC, and more advanced techniques may be indicated for assessment of cervical lymph node involvement and deciding on the most efficient surgical approach in patients with oral SCC.